2022
DOI: 10.1007/s11665-022-07654-y
|View full text |Cite
|
Sign up to set email alerts
|

Study of Microstructure, Mechanical Properties, and Corrosion Behavior of As-Cast Ni-Ti and Ti-6Al-4V Alloys

Abstract: Ni-Ti and Ti-6Al-4V alloys were cast as ingots using vacuum arc remelting furnace. The microstructure of as-cast Ni-Ti alloy consists of NiTi matrix as well as Ti2Ni dendrites. As-cast Ti-6Al-4V alloy revealed a structure composed of equiaxed β grains and varied α-phase morphologies. Ti-6Al-4V alloy registered maximum ultimate compressive strength of 2042 MPa, and also reported large reduction in height (18%). However, Ni-Ti alloy showed minimum ultimate compressive strength of 1804 MPa and low reduction in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 50 publications
1
10
1
Order By: Relevance
“…The slight decrease in the hardness after quenching may be attributed to the absence of α″ phase. It has been reported that the presence of porosity reduces the elastic modulus of a component, however, it can also lead to local stress concentrations which decrease the strength, hardness, and ductility of the alloys 35 In comparison to the sample in the as-cast condition, a significant increase in hardness is observed in the TMF3 alloy upon quenching. Since the solid solution strengthening effect is common in both samples containing high Fe, it is highly possible that rapid oxidation of the intermetallic B2 phase could be responsible for increased hardness.…”
Section: Resultsmentioning
confidence: 97%
“…The slight decrease in the hardness after quenching may be attributed to the absence of α″ phase. It has been reported that the presence of porosity reduces the elastic modulus of a component, however, it can also lead to local stress concentrations which decrease the strength, hardness, and ductility of the alloys 35 In comparison to the sample in the as-cast condition, a significant increase in hardness is observed in the TMF3 alloy upon quenching. Since the solid solution strengthening effect is common in both samples containing high Fe, it is highly possible that rapid oxidation of the intermetallic B2 phase could be responsible for increased hardness.…”
Section: Resultsmentioning
confidence: 97%
“…In a study by Elshaer and Ibrahim, they observed that a TiO 2 layer was dissolved in the presence of chloride ions (Elshaer and Ibrahim, 2022). Oxide layers are a kind of protection of metal materials against corrosion caused by a chloride environment.…”
Section: Corrosion Results Of Niti Alloysmentioning
confidence: 99%
“…They also noted that pitting corrosion occurs predominantly in NiTi alloy (Kuphasuk et al , 2001). Elshaer and Ibrahim stated that in corrosion tests with 0.9% NaCl solution with NiTi and Ti-6Al-4V alloys produced by the vacuum melting method, Ti-6Al-4V alloy has better corrosion resistance than NiTi alloy (Elshaer and Ibrahim, 2022). The best electrochemical performance is defined as the greatest polarization resistance and the lowest corrosion current density (Wei and Dejun, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a wide range of microstructures and mechanical properties can be obtained to customize applications 7 . TC21 is thought to be a strong competitor and replacement for the well-known Ti-alloy Ti-6Al-4V (Ti64) 8 . Some call Ti64 a workhorse titanium industry alloy, it dominates 50% of the global market 6 .…”
Section: Modeling Of Wear Resistance For Tc21 Ti-alloy Using Response...mentioning
confidence: 99%